2019
DOI: 10.1021/acs.joc.9b00608
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis and Key Intermediate Isolation in Ni2Dy2 Catalyst Development in the Domino Ring-Opening Electrocyclization Reaction of Furfural and Amines

Abstract: Solventfree synthesis and key intermediate isolation in Ni2Dy2 catalyst development in the domino ringopening electrocyclization reaction of furfural and amines Article (Accepted Version) http://sro.sussex.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The authors synthesised and characterised a copper(I) complex with tert-butyldiallylphosphine ligands. Single X-ray diffraction studies identified a cubane-like structure of the copper complex of formula [CuCl{κ 1 (P)-t Bu-P(CH 2 CH = CH 2 ) 2 }] 4 (5). However, variable temperature NMR studies indicated a dynamic behaviour in solution generated by the cubane chair isomerisation due to the low stability of the cube-like structure caused by the strong strain of the Cu 4 Cl 4 core for steric reasons.…”
Section: Scheme 57 (Left)mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors synthesised and characterised a copper(I) complex with tert-butyldiallylphosphine ligands. Single X-ray diffraction studies identified a cubane-like structure of the copper complex of formula [CuCl{κ 1 (P)-t Bu-P(CH 2 CH = CH 2 ) 2 }] 4 (5). However, variable temperature NMR studies indicated a dynamic behaviour in solution generated by the cubane chair isomerisation due to the low stability of the cube-like structure caused by the strong strain of the Cu 4 Cl 4 core for steric reasons.…”
Section: Scheme 57 (Left)mentioning
confidence: 99%
“…It is unclear whether these principles apply to polycomponent reactions promoted by well-characterised species. Several studies on well-characterised catalysts, i.e., those in which the active species is known, suggest that these catalysts [5][6][7][8][9][10][11][12][13]:…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, microwave irradiation, tosylamine, and the ChCl/urea system were also used as metal-free procedures. In parallel, a series of heteronuclear {Ni­(II) 2 Dy­(III) 2 L 4 (DMF) 6 ] 2­(OTf)} coordination complexes (where Ln = Y, Dy; and H 2 L = ( E )-2-(((2-hydroxyphenyl)­imino)­methyl)-6-methoxyphenol), as well as MIL series of MOF, with Fe-MIL-100 and -101 and a Dy­(III) complex, were reported to facilitate this reaction under mild conditions and with low catalyst loadings (Scheme , lower). It is worth noting that, in most of the above protocols, the reaction scope was limited to secondary amines; however, only sporadic examples applied to primary amines, i.e., aniline or 2-fluoroaniline with 3-bromofurfural …”
Section: Introductionmentioning
confidence: 99%
“…To expand our understanding of tuning the performance of DASA based systems, we targeted structural modifications on the triene backbone. Substitution on the 3-position of the backbone has been shown to favour the closed form both in donor–acceptor Stenhouse adducts as well as Stenhouse Salts, 28,29 however other substitutions have been largely overlooked. We envisioned that by finding a position on the triene backbone which increases the relative energy of the stable closed form ( i.e.…”
mentioning
confidence: 99%